Method for preparing vanadium electrolyte from high-arsenic vanadium-containing material
Through three -stage coordination of deep arsenic methods, the problem of deep arsenic and electrolytes of high arsenic materials contains high arsenic materials, and realized the production of low -cost and environmentally friendly electrolytes.
Patent Information
- Application Number
- CN202411504455.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-26
AI Technical Summary
It is difficult to achieve deep arsenic dearrheology of high arsenic vanadium-containing materials and prepare high-purity vanadium electrolytes in the prior art, and traditional methods have problems of high cost and environmental pollution.
Three-segment coordination of deep arsenic methods, including restoring roasting, crystallization purification and sulfurization precipitation, gradually realize the deep arsenic de-arsenal of high arsenic ingredients, and prepare the electro-electrolytes that meet the GB/T 37204-2018 standards.
The deep arsenic of high arsenic containing ravioli materials reduces the cost of raw materials for the production of electrolytes, and avoids environmental pollution. The arsenic content in the obtained electrolytes is less than 0.5 PPM, which meets industry standards.
Smart Images

Figure CN119349633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of vanadium electrolyte, in particular to a method for preparing vanadium electrolyte by utilizing high-arsenic vanadium-containing material. Background Art
[0002] High-arsenic vanadium-containing materials refer to solid substances such as crude V2O5, red vanadium, ammonium polyvanadate, ammonium metavanadate, etc., with an arsenic content higher than 0.1 wt%, which are generally derived from waste SCR catalysts, stone coal, bauxite and other raw materials. Due to the high arsenic content, high-arsenic vanadium-containing materials are cheap but difficult to use.
[0003] The electrolyte of all-vanadium flow battery is a high-value vanadium product, which is mainly prepared with expensive high-purity V2O5 as raw material. However, this also leads to a high cost of vanadium electrolyte. If high-arsenic vanadium-containing materials are used to produce vanadium electrolyte, it can not only solve the problem of high-value utilization of high-arsenic vanadium-containing materials, but also reduce the cost of raw materials for vanadium electrolyte production. However, vanadium electrolyte directly determines the energy storage capacity and performance of vanadium batteries. The national standard GB / T 37204-2018 has very strict requirements on arsenic concentration in vanadium electrolysis, which should be less than 1 ppm. Therefore, the production of vanadium electrolyte from high-arsenic vanadium-containing materials must be purified and de-arsenicated.
[0004] At present, the methods for purifying crude vanadium include ammonium precipitation, chlorination, crystallization, cation replacement, etc., and the methods for preparing vanadium electrolyte with high-purity vanadium include chemical reduction, electrolytic reduction, extraction, etc. However, none of these methods involve how to achieve deep arsenic removal from solid high-arsenic vanadium-containing raw materials and prepare vanadium electrolyte. Chinese patent CN 116536513 A discloses a method for separating and removing impurities arsenic from vanadium-containing solution raw materials (1-100 mg / L) for producing electrolyte for all-vanadium liquid flow batteries. Calcium chloride and soluble barium salt are added to the vanadium-containing solution, and arsenic and impurities such as phosphorus and silicon are removed at one time by filtering to obtain a deeply purified and arsenic-free vanadium-containing solution. This method has a good arsenic removal effect, but calcium and barium ions are introduced, and further impurities removal by extraction is still required in the future. If the arsenic concentration in the solution is high, it will lead to a large loss of vanadium, which is not suitable for deep arsenic removal of high-arsenic vanadium solution raw materials. The ion exchange method can treat vanadium-containing solutions with low arsenic content, but too high arsenic will cause ion exchange resin poisoning and inactivation. At the same time, the above method is only applicable to the dearsenication of vanadium-containing solutions, and is not applicable to the deep dearsenication of solid high-arsenic vanadium-containing raw materials and the preparation of vanadium electrolytes.
[0005] The Chinese invention patent application with publication number CN 115747525 A provides a method for purifying crude vanadium by crystallization, wherein crude vanadium is dissolved in alkaline solution until saturated, and ammonium salt is added to the saturated solution for vanadium precipitation treatment, and ammonium metavanadate crystals are precipitated. The ammonium metavanadate crystals are further purified by dissolution and cooling crystallization to obtain ammonium metavanadate with a purity of not less than 99%. However, this method introduces ammonium salts, produces ammonia nitrogen wastewater that is difficult to treat, and has great harm to the environment. The Chinese invention patent application with publication number CN 116404220A provides a method for preparing a high-concentration vanadium electrolyte by crystallization purification of vanadates-chemical reduction, using crude vanadium and other vanadium-containing materials as raw materials, and obtaining high-purity vanadates by alkali dissolution-crystallization purification, and the high-purity vanadates are then prepared by chemical reduction to prepare vanadium electrolytes. Both of the above methods do not clearly define the arsenic content in crude vanadium, and do not specifically provide a deep arsenic removal method, so they are not suitable for deep arsenic removal of high-arsenic vanadium-containing raw materials and preparation of vanadium electrolytes.
[0006] In summary, the existing methods for purifying vanadium-containing raw materials and preparing electrolytes are not suitable for deep arsenic removal from high-arsenic vanadium-containing raw materials and preparation of vanadium electrolytes. Therefore, a method for deep arsenic removal from high-arsenic vanadium-containing raw materials and preparation of vanadium electrolytes is urgently needed. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, aiming to achieve the purification and impurity removal of the high-arsenic vanadium-containing material and the preparation of a vanadium electrolyte, so that the obtained vanadium electrolyte meets the requirements of GB / T 37204-2018 for a first-class quadrivalent vanadium electrolyte, while reducing the production cost of the vanadium electrolyte.
[0008] According to one aspect of the present invention, a method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material is provided, comprising the following steps:
[0009] 1) After mixing the high-arsenic vanadium-containing material and the arsenic removal reducing agent in a ratio of 2-9 times the theoretical content of the arsenic removal reducing agent required for reducing As(V) to As(III), the mixture is pressed into blocks at a pressure of 50-150 MPa, and calcined at a temperature range of 200-700°C for 1-6 h in an inert atmosphere to obtain a low-arsenic vanadium-containing material;
[0010] 2) using alkaline solution to leach low-arsenic vanadium-containing material at 20-99°C, stirring the solution at a speed of 50-200 r / min for 1-4h, filtering to obtain a vanadate solution, then cooling the vanadate solution to 0-40°C at a rate of 0.1-5°C / min, stirring the solution at a rate of ≤400 r / min during the cooling period, filtering to obtain vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with vanadate crystals as raw materials to repeat step 2) multiple times to obtain high-purity vanadate crystals;
[0011] 3) dissolving the high-purity vanadate crystals obtained in step 2) in acid, adjusting the pH value to 1-5, adding a reducing agent according to 1.2-3 times the theoretical content of the reducing agent required for reducing V(V) to V(IV), reacting at 20-99° C. for 0.5-5 h to obtain a V(IV) solution, adjusting the pH value of the V(IV) solution to -1-5, adding an arsenic removal precipitant in multiple times according to 2-8 times the theoretical amount of the arsenic removal precipitant required for removing As(III), reacting at 20-99° C. for 0.5-2 h, filtering to obtain an arsenic removal solution, adjusting the pH value of the arsenic removal solution to 5-12, filtering to obtain a VO(OH)2 solid, washing the VO(OH)2 solid with acid and water, and dissolving the washed VO(OH)2 with acid to prepare a vanadium electrolyte; wherein the reducing agent comprises one or more of sodium sulfide, elemental sulfur, sulfur dioxide, sulfite, oxalic acid, oxalate, glucose, fructose, sucrose, and formic acid.
[0012] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, the high-arsenic vanadium-containing material comprises one or more of red vanadium with an arsenic content ≥0.1 wt%, crude V2O5, ammonium polyvanadate, and ammonium metavanadate.
[0013] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, the high-arsenic vanadium-containing material contains 70-98wt% V2O5; the high-arsenic vanadium-containing material is obtained by the vanadium extraction process of waste SCR catalyst, stone coal and / or bauxite.
[0014] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, in step 1), the arsenic removal reducing agent includes one or more of metallic vanadium, VO, V2O3, and VO2.
[0015] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, in step 1), the inert atmosphere is an argon atmosphere.
[0016] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, in step 2), the alkali solution includes one or more of NaOH and KOH solutions with a concentration of 50-500 g / L.
[0017] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, the multiple times in step 2) is 2 to 4 times.
[0018] As a preferred embodiment of the method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material of the present invention, the pH value is adjusted by adding one or more acids including sulfuric acid and hydrochloric acid to the solution for adjustment when the pH value needs to be lowered; and adding one or more bases including NaOH, KOH, and NH3 to the solution for adjustment when the pH value needs to be increased.
[0019] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing materials of the present invention, the arsenic removal precipitant includes one or more of sodium sulfide, potassium sulfide, ammonium sulfide, hydrogen sulfide, and thiourea. The theoretical amount of the arsenic removal precipitant required for removing As(III) is specifically the theoretical amount of the arsenic removal precipitant required for As(III) to react with the arsenic removal precipitant to generate As2S3.
[0020] As a preferred embodiment of the method for preparing vanadium electrolyte using high-arsenic vanadium-containing material of the present invention, the multiple times in step 3) is 3 to 5 times.
[0021] As a preferred embodiment of the method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material of the present invention, in step 3), the reagent used for the acid washing is dilute sulfuric acid with a pH of 5 to 7, the number of washing times for the acid washing is 1 to 3 times, and the number of washing times for the water washing is 2 to 3 times; the reagent used for the acid dissolution is sulfuric acid with a concentration of 4 to 6 mol / L.
[0022] The present invention uses three-stage coordinated deep arsenic removal and synchronous preparation of vanadium electrolyte. Red vanadium, crude V2O5, ammonium polyvanadate and / or ammonium metavanadate with an arsenic content higher than 0.1 wt% are subjected to reduction roasting, and As2O5 therein is reduced to As2O3 and removed in gaseous form to achieve one-stage arsenic removal; the roasted material is dissolved, and cooling crystallization is used to achieve two-stage arsenic removal, and other impurity elements are removed simultaneously; the purified high-purity vanadate is subjected to reduction acid leaching, and then an arsenic removal precipitant is added to achieve three-stage deep arsenic removal to obtain a V(IV) solution. The V(IV) solution is hydrolyzed to remove sodium and then acid-dissolved to obtain a vanadium electrolyte.
[0023] In the technical solution of the present invention, all contents are by mass unless otherwise specified, As(V) refers to pentavalent arsenic, As(III) refers to trivalent arsenic, V(V) refers to pentavalent vanadium, and V(IV) refers to tetravalent vanadium.
[0024] Compared with the prior art, this invention has the following beneficial effects:
[0025] 1. The present invention achieves deep arsenic removal from high-arsenic vanadium-containing materials through reduction roasting, crystallization purification, and sulfide precipitation. The amount of arsenic removed meets the requirements for preparing vanadium electrolyte. Compared with chemical precipitation, ion exchange, single crystallization and other processes, arsenic and other impurities have good deep removal effects, and can be further prepared to meet the requirements of GB / T 37204-2018 for first-class 4-valent vanadium electrolyte. The impurity content As in the vanadium electrolyte obtained based on the solution of the present invention is ≤0.5 ppm.
[0026] 2. The present invention uses high-arsenic vanadium-containing materials as raw materials. Compared with other industrial vanadium principles such as crude vanadium that does not contain arsenic, the price is low, and no highly polluting and high-cost reagents such as ammonium salts, organic extractants, and chlorine are required throughout the process. The preparation process is clean and low-cost.
[0027] 3. The arsenic removal reducing agent and precipitating agent used in the present invention are all original elements in the solution system, and no other impurity elements are introduced, and have no effect on the purity of the vanadium electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation method of the present invention
[0029] Figure 2 Actual picture of vanadium electrolyte obtained by the preparation method of the present invention DETAILED DESCRIPTION
[0030] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V53%, Al 0.1%, As 0.55%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0033] 1) After mixing 100g of high-arsenic vanadium-containing material with 4.4g V2O3 (8 times the theoretical reaction amount), the mixture was pressed into blocks under a pressure of 100MPa, and calcined at a temperature range of 700°C for 4h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.05 wt%;
[0034] 2) dissolving the low-arsenic vanadium-containing material in 1L of a 300g / L NaOH solution at 60°C for leaching, stirring at a rate of 200r / min, leaching for 2h, filtering to obtain a sodium vanadate solution, then cooling the sodium vanadate solution to 10°C at a rate of 0.5°C / min, stirring the solution at a rate of 100r / min during the cooling period, filtering to obtain sodium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with sodium vanadate crystals as a raw material and repeating step 2) twice to obtain 161g of high-purity sodium vanadate crystals with an arsenic content of 0.01wt% and a purity of 99.9%;
[0035] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 0, 79.2 g of oxalic acid is added, and the reaction is carried out at 60° C. for 2 h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 2 with NaOH, and 0.125 g of Na2S (0.041 g + 0.042 g + 0.042 g) is added in 3 portions, and the reaction is carried out at 60° C. for 1 h, and the arsenic-free solution having an As content of 5.5 ppm is obtained by filtration, the pH value of the arsenic-free solution is adjusted to 6 with NaOH, and VO(OH)2 solid is obtained by filtration, the VO(OH)2 solid is washed twice with dilute sulfuric acid having a pH of 6, and then washed twice with pure water, and dissolved in 500 ml of a 4 mol / L sulfuric acid solution to obtain a vanadium concentration of 1.6 mol / L and a sulfate concentration of 3.9 mol / L. Vanadyl sulfate electrolyte.
[0036] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.2 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quaternary electrolytes.
[0037] Example 2
[0038] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V44%, Al 0.2%, As 0.34%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0039] 1) After mixing 200g of high-arsenic vanadium-containing material and 0.74g of elemental vanadium powder, the mixture was pressed into blocks under a pressure of 120MPa, and calcined at a temperature range of 500°C for 2h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.07wt%;
[0040] 2) dissolving the low-arsenic vanadium-containing material in 1.6L of a 400g / L KOH solution at 80°C for leaching, stirring at a rate of 200r / min, leaching for 1h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 20°C at a rate of 2°C / min, stirring the solution at a rate of 50r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) twice to obtain 280g of high-purity potassium vanadate crystals with an arsenic content of 0.015wt% and a purity of 99.93%;
[0041] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to -1, 150g of sodium sulfite is added, and the reaction is carried out at 80°C for 1h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 0 with KOH, and 0.72g of K2S (0.144g each time) is added in 5 times, and the reaction is carried out at 80°C for 1h, and the arsenic-free solution having an As content of 4.2ppm is obtained by filtration, and the pH value of the arsenic-free solution is adjusted to 7 with KOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed twice with dilute sulfuric acid having a pH of 6.5, and then washed twice with pure water, and dissolved in 400ml of 5mol / L sulfuric acid solution to obtain a vanadium concentration of 2mol / L and a sulfate concentration of 4.8mol / L. Vanadyl sulfate electrolyte.
[0042] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.5 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quadrivalent electrolytes.
[0043] Example 3
[0044] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V42%, Al 0.1%, As 0.44%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0045] 1) After mixing 200 g of high-arsenic vanadium-containing material with 2.096 g of VO, the mixture was pressed into a block under a pressure of 50 MPa, and calcined at a temperature range of 300 ° C for 6 h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.04 wt%;
[0046] 2) The low-arsenic vanadium-containing material was dissolved in 1.5L of a 250g / L NaOH solution at 90°C for leaching, with a stirring rate of 50r / min and a leaching time of 3h. The sodium vanadate solution was filtered to obtain a sodium vanadate solution, and then the sodium vanadate solution was cooled to 5°C at a rate of 5°C / min, and the solution was stirred at a rate of 300r / min during the cooling period. After cooling, the sodium vanadate crystals were filtered to obtain sodium vanadate crystals, and then the sodium vanadate crystals were used to replace the low-arsenic vanadium-containing material as a raw material to repeat step 2) 4 times to obtain 250g of high-purity sodium vanadate crystals with an arsenic content of 0.025wt% and a purity of 99.94%;
[0047] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 3. 10.86 g of elemental sulfur is added, and the reaction is carried out at 30° C. for 5 hours to obtain a V(IV) solution. The pH value of the V(IV) solution is adjusted to 4 with NaOH, and then 0.17 g of (NH4)2S (0.0425 g + 0.0425 g + 0.0425 g + 0.0425 g) is added in 4 portions, and the reaction is carried out at 30° C. for 2 hours. The arsenic-free solution having an As content of 6.7 ppm is obtained by filtering, and the pH value of the arsenic-free solution is adjusted to 10 with NaOH, and VO(OH)2 solid is obtained by filtering. The VO(OH)2 solid is washed once with dilute sulfuric acid having a pH of 6.5, and then washed 3 times with pure water, and dissolved in 530 ml of a 5 mol / L sulfuric acid solution to obtain a vanadium concentration of 2.3 mol / L and a sulfate concentration of 4.8 mol / L. Vanadyl sulfate electrolyte.
[0048] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.3 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quadrivalent electrolytes.
[0049] Example 4
[0050] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V51%, Al 0.1%, As 1.57%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0051] 1) After 50g of high-arsenic vanadium-containing material and 10.42g of VO2 were mixed, the mixture was pressed into blocks under a pressure of 100MPa, and calcined at a temperature range of 400°C for 5h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.08wt%;
[0052] 2) dissolving the low-arsenic vanadium-containing material in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, stirring at a rate of 50 r / min, and leaching for 1 h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 2° C. at a rate of 8° C. / min, stirring the solution at a rate of 80 r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) 4 times to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.07 wt% and a purity of 99.9%;
[0053] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 2.5, 48g of potassium oxalate is added, and the reaction is carried out at 99°C for 0.5h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 0 with dilute sulfuric acid, and 1.232g of K2S (0.41g+0.411g+0.411g) is added in three portions, and the reaction is carried out at 99°C for 1h, and the arsenic-free solution having an As content of 4.5ppm is obtained by filtration, the pH value of the arsenic-free solution is adjusted to 5 with KOH, and VO(OH)2 solid is obtained by filtration, the VO(OH)2 solid is washed once with dilute sulfuric acid having a pH of 6.5, and then washed three times with pure water, and dissolved in 200ml of 6mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte having a vanadium concentration of 2mol / L and a sulfate concentration of 5.8mol / L.
[0054] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.5 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quadrivalent electrolytes.
[0055] Example 5
[0056] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V48%, Al 0.1%, As 0.12%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0057] 1) After 300g of high-arsenic vanadium-containing material and 3.24g of V2O3 were mixed, the mixture was pressed into a block under a pressure of 150MPa, and calcined at a temperature range of 700°C for 1h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.01wt%;
[0058] 2) dissolving the low-arsenic vanadium-containing material in 2.7 L of a 500 g / L NaOH solution at 99° C. for leaching, stirring at a rate of 200 r / min, and leaching for 2 h, filtering to obtain a sodium vanadate solution, then cooling the sodium vanadate solution to 40° C. at a rate of 10° C. / min, stirring the solution at a rate of 10 r / min during the cooling period, filtering to obtain sodium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with sodium vanadate crystals as a raw material and repeating step 2) twice to obtain 482 g of high-purity sodium vanadate crystals with an arsenic content of 0.01 wt% and a purity of 99.95%;
[0059] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 5. 58.7 g of glucose is added, and the reaction is carried out at 20° C. for 5 h to obtain a V(IV) solution. The pH value of the V(IV) solution is adjusted to 5 with dilute sulfuric acid, and 0.225 g of Na2S (0.045 g each time) is added in 5 times, and the reaction is carried out at 20° C. for 2 h. The arsenic-free solution having an As content of 3.7 ppm is obtained by filtration. The pH value of the arsenic-free solution is adjusted to 12 with NaOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution having a pH of 6.5, and then washed 3 times with pure water, and dissolved with 550 ml of a 6 mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte having a vanadium concentration of 3.5 mol / L and a sulfate concentration of 5.8 mol / L.
[0060] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.1 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quadrivalent electrolytes.
[0061] Example 6
[0062] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V43%, Al 0.1%, As 0.77%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0063] 1) After 100 g of high-arsenic vanadium-containing material and 0.42 g of elemental vanadium are mixed, the mixture is pressed into a block under a pressure of 50 MPa, and then calcined at a temperature range of 200° C. for 6 h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.05 wt%;
[0064] 2) The low-arsenic vanadium-containing material was dissolved in 750 mL of a 50 g / L KOH solution at 20° C., the stirring rate was 200 r / min, the leaching time was 4 h, and the potassium vanadate solution was filtered to obtain a potassium vanadate solution, and then the potassium vanadate solution was cooled to 1° C. at a rate of 0.1° C. / min, and the solution was stirred at a rate of 400 r / min during the cooling period. After cooling, potassium vanadate crystals were filtered to obtain potassium vanadate crystals, and then the low-arsenic vanadium-containing material was replaced with potassium vanadate crystals as a raw material, and step 2) was repeated twice to obtain 120 g of high-purity potassium vanadate crystals with an arsenic content of 0.06 wt% and a purity of 99.9%;
[0065] 3) The high-purity potassium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to -1, 15 g of formic acid is added, and the reaction is carried out at 50°C for 2 hours to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 5 with KOH, and 1.26 g of K2S (0.315 g each time) is added in 4 times, and the reaction is carried out at 50°C for 2 hours, and the arsenic-free solution with an As content of 6 ppm is obtained by filtration, and the pH value of the arsenic-free solution is adjusted to 9 with KOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed twice with a dilute sulfuric acid solution with a pH of 6.5, and then washed three times with pure water, and dissolved in 180 ml of a 5.5 mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte with a vanadium concentration of 2.5 mol / L and a sulfate concentration of 5.2 mol / L.
[0066] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.2 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quaternary electrolytes.
[0067] Example 7
[0068] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V52%, Al 0.1%, As 0.84%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0069] 1) After 50g of high-arsenic vanadium-containing material and 6.5g of VO2 were mixed, the mixture was pressed into a block under a pressure of 100MPa, and calcined at a temperature range of 450°C for 5h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.07wt%;
[0070] 2) dissolving the low-arsenic vanadium-containing material in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, stirring at a rate of 50 r / min, and leaching for 1 h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 2° C. at a rate of 8° C. / min, stirring the solution at a rate of 80 r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) twice to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.06 wt% and a purity of 99.92%;
[0071] 3) The high-purity potassium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 2.5, 48g of potassium oxalate is added, and the reaction is carried out at 99°C for 0.5h to obtain a V(IV) solution, and the pH value of the V(IV) solution is adjusted to 0 with dilute sulfuric acid, and then 1.056g of K2S (0.352g each time) is added in 3 times, and the reaction is carried out at 99°C for 1h, and the arsenic-free solution with an As content of 4ppm is obtained by filtration, and the pH value of the arsenic-free solution is adjusted to 5 with KOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution with a pH of 6.5, and then washed 3 times with pure water, and dissolved with 200ml of 6mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte with a vanadium concentration of 2mol / L and a sulfate concentration of 5.8mol / L.
[0072] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this example was 0.4 ppm, which meets the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Liquid Flow Batteries" for first-class quadrivalent electrolytes.
[0073] Comparative Example 1
[0074] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V53%, Al 0.1%, As 0.55%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0075] 1) After mixing 100g of high-arsenic vanadium-containing material with 0.55g V2O3 (1 times the theoretical reaction amount), the mixture was pressed into blocks under a pressure of 100MPa, and calcined at a temperature range of 700°C for 4h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.32 wt%;
[0076] 2) dissolving the low-arsenic vanadium-containing material in 1L of a 300g / L NaOH solution at 60°C for leaching, stirring at a rate of 200r / min, leaching for 2h, filtering to obtain a sodium vanadate solution, then cooling the sodium vanadate solution to 10°C at a rate of 0.5°C / min, stirring the solution at a rate of 100r / min during the cooling period, filtering to obtain sodium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with sodium vanadate crystals as a raw material and repeating step 2) twice to obtain 161g of high-purity sodium vanadate crystals with an arsenic content of 0.16wt% and a purity of 99.74%;
[0077] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 0, 79.2 g of oxalic acid is added, and the reaction is carried out at 60° C. for 2 h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 2 with NaOH, and 0.125 g of Na2S (0.041 g + 0.042 g + 0.042 g) is added in 3 portions, and the reaction is carried out at 60° C. for 1 h, and the arsenic-free solution having an As content of 15.8 ppm is obtained by filtration, the pH value of the arsenic-free solution is adjusted to 6 with NaOH, and VO(OH)2 solid is obtained by filtration, the VO(OH)2 solid is washed twice with dilute sulfuric acid having a pH of 6, and then washed twice with pure water, and dissolved in 500 ml of a 4 mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte having a vanadium concentration of 1.6 mol / L and a sulfate concentration of 3.9 mol / L.
[0078] It was determined that the As content in the vanadium sulfate electrolyte prepared in this comparative example was 3.3ppm, which did not meet the requirements of GB / T 37204-2018 "Electrolyte for All-Vanadium Redox Flow Battery" for first-class 4-valent electrolyte. Compared with Example 1, due to the small amount of arsenic removal reducing agent added in this comparative example, most of the arsenic in the high-arsenic vanadium-containing material failed to react with the reducing agent to form gaseous As2O3 and was removed, resulting in a high arsenic content in the low-arsenic vanadium-containing material. The subsequent crystallization and sulfidation precipitation process was difficult to completely remove the arsenic, which ultimately resulted in an excessively high arsenic content in the vanadium electrolyte.
[0079] Comparative Example 2
[0080] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V44%, Al 0.2%, As 0.34%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0081] 1) After mixing 200g of high-arsenic vanadium-containing material and 0.74g of elemental vanadium powder, the mixture was pressed into blocks under a pressure of 120MPa, and calcined at a temperature range of 150°C for 2h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.33wt%;
[0082] 2) dissolving the low-arsenic vanadium-containing material in 1.6L of a 400g / L KOH solution at 80°C for leaching, stirring at a rate of 200r / min, leaching for 1h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 20°C at a rate of 2°C / min, stirring the solution at a rate of 50r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) twice to obtain 280g of high-purity potassium vanadate crystals with an arsenic content of 0.13wt% and a purity of 99.8%;
[0083] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to -1, 150g of sodium sulfite is added, and the reaction is carried out at 80°C for 1h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 0 with KOH, and 0.72g of K2S (0.144g each time) is added in 5 times, and the reaction is carried out at 80°C for 1h, and the arsenic-free solution having an As content of 22.1ppm is obtained by filtration, and the pH value of the arsenic-free solution is adjusted to 7 with KOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed twice with dilute sulfuric acid having a pH of 6.5, and then washed twice with pure water, and dissolved in 400ml of 5mol / L sulfuric acid solution to obtain a vanadium concentration of 2mol / L and a sulfate concentration of 4.8mol / L. Vanadyl sulfate electrolyte.
[0084] It was determined that the As content in the vanadium sulfate electrolyte prepared in this comparative example was 4.5ppm, which did not meet the requirements of GB / T 37204-2018 "Electrolyte for All-Vanadium Redox Flow Battery" for first-class 4-valent electrolyte. Compared with Example 2, the reduction roasting temperature in this comparative example was too low, and the reaction temperature of As2O5 and the arsenic removal reducing agent was not reached, resulting in the arsenic in the high-arsenic vanadium-containing material failing to react with the reducing agent to form gaseous As2O3 and be removed, and the arsenic content in the low-arsenic vanadium-containing material was relatively high. The subsequent crystallization and sulfidation precipitation process was difficult to completely remove the arsenic, which ultimately resulted in the arsenic content of the vanadium electrolyte being too high.
[0085] Comparative Example 3
[0086] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V42%, Al 0.1%, As 0.44%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0087] 1) After mixing 200 g of high-arsenic vanadium-containing material with 2.096 g of VO, the mixture was pressed into a block under a pressure of 50 MPa, and calcined at a temperature range of 300 ° C for 0.5 h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.24 wt%;
[0088] 2) The low-arsenic vanadium-containing material was dissolved in 1.5L of a 250g / L NaOH solution at 90°C for leaching, with a stirring rate of 50r / min and a leaching time of 3h. The sodium vanadate solution was filtered to obtain a sodium vanadate solution, and then the sodium vanadate solution was cooled to 5°C at a rate of 5°C / min, and the solution was stirred at a rate of 300r / min during the cooling period. After cooling, the sodium vanadate crystals were filtered to obtain sodium vanadate crystals, and then the sodium vanadate crystals were used as raw materials instead of the low-arsenic vanadium-containing material to repeat step 2) 4 times to obtain 250g of high-purity sodium vanadate crystals with an arsenic content of 0.12wt% and a purity of 99.82%;
[0089] 3) The high-purity sodium vanadate crystals obtained in step 2) were dissolved in dilute sulfuric acid, and the pH value was adjusted to 3. 10.86 g of elemental sulfur was added, and the reaction was carried out at 30° C. for 5 h to obtain a V(IV) solution. The pH value of the V(IV) solution was adjusted to 4 with NaOH, and 0.17 g of (NH4)2S (0.0425 g + 0.0425 g + 0.0425 g + 0.0425 g) was added in 4 portions, and the reaction was carried out at 30° C. for 2 h. The arsenic-free solution having an As content of 13.2 ppm was obtained by filtration. The pH value of the arsenic-free solution was adjusted to 10 with NaOH, and VO(OH)2 solid was obtained by filtration. The VO(OH)2 solid was washed once with dilute sulfuric acid having a pH of 6.5, and then washed 3 times with pure water, and dissolved in 530 ml of a 5 mol / L sulfuric acid solution to obtain a vanadium concentration of 2.3 mol / L and a sulfate concentration of 4.8 mol / L. Vanadyl sulfate electrolyte.
[0090] It was determined that the As content in the vanadium sulfate electrolyte prepared in this comparative example was 1.5 ppm, which did not meet the requirements of GB / T 37204-2018 "Electrolyte for All-Vanadium Liquid Flow Battery" for first-class 4-valent electrolyte. Compared with Example 3, due to the short reduction roasting time in this comparative example, part of the arsenic in the high-arsenic vanadium-containing material failed to react with the reducing agent in time to form gaseous As2O3 and be removed, resulting in a high arsenic content in the low-arsenic vanadium-containing material. The subsequent crystallization and sulfidation precipitation process is difficult to completely remove the arsenic, which ultimately leads to an excessively high arsenic content in the vanadium electrolyte.
[0091] Comparative Example 4
[0092] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V51%, Al 0.1%, As1.57%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0093] 1) After 50g of high-arsenic vanadium-containing material and 10.42g of VO2 were mixed, the mixture was pressed into blocks under a pressure of 100MPa, and calcined at a temperature range of 400°C for 5h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.08wt%;
[0094] 2) dissolving the low-arsenic vanadium-containing material in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, stirring at a rate of 50 r / min, and leaching for 1 h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 2° C. at a rate of 8° C. / min, stirring the solution at a rate of 80 r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) 4 times to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.07 wt% and a purity of 99.9%;
[0095] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 2.5, 48g of potassium oxalate is added, and the reaction is carried out at 99°C for 0.5h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 0 with dilute sulfuric acid, and 0.154g of K2S (0.051g+0.051g+0.052g, 1 times the theoretical reaction amount) is added in 3 times, and the reaction is carried out at 99°C for 1h, and the arsenic-free solution with an As content of 36ppm is obtained by filtering, and the pH value of the arsenic-free solution is adjusted to 5 with KOH, and VO(OH)2 solid is obtained by filtering. The VO(OH)2 solid is washed once with dilute sulfuric acid with a pH of 6.5, and then washed 3 times with pure water, and dissolved in 200ml of 6mol / L sulfuric acid solution to obtain a vanadium concentration of 2mol / L and a sulfate concentration of 5.8mol / L. Vanadyl sulfate electrolyte.
[0096] The As content in the vanadyl sulfate electrolyte prepared in this comparative example was determined to be 5 ppm, which did not meet the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Redox Flow Batteries" for first-class 4-valent electrolytes. Compared with Example 4, the amount of precipitant added in this comparative example was too low, and the As in the V(IV) solution could not be removed. 3+ Deep removal causes arsenic ions to be mixed in VO(OH)2 and enter the vanadium electrolyte, causing the arsenic content of the vanadium electrolyte to exceed the standard.
[0097] Comparative Example 5
[0098] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V48%, Al 0.1%, As 0.12%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0099] 1) After 300g of high-arsenic vanadium-containing material and 3.24g of V2O3 were mixed, the mixture was pressed into a block under a pressure of 150MPa, and calcined at a temperature range of 700°C for 1h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.01wt%;
[0100] 2) dissolving the low-arsenic vanadium-containing material in 2.7 L of a 500 g / L NaOH solution at 99° C. for leaching, stirring at a rate of 200 r / min, and leaching for 2 h, filtering to obtain a sodium vanadate solution, then cooling the sodium vanadate solution to 40° C. at a rate of 10° C. / min, stirring the solution at a rate of 10 r / min during the cooling period, filtering to obtain sodium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with sodium vanadate crystals as a raw material and repeating step 2) twice to obtain 482 g of high-purity sodium vanadate crystals with an arsenic content of 0.01 wt% and a purity of 99.95%;
[0101] 3) The high-purity sodium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 5, 58.7 g of glucose is added, and the reaction is carried out at 20° C. for 5 hours to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 9 with NaOH, and 0.225 g of Na2S (0.045 g each time) is added in 5 times, and the reaction is carried out at 20° C. for 2 hours, and the arsenic-free solution with an As content of 26.3 ppm is obtained by filtration, and the pH value of the arsenic-free solution is adjusted to 12 with NaOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution with a pH of 6.5, and then washed 3 times with pure water, and dissolved in 550 ml of a 6 mol / L sulfuric acid solution to obtain a vanadium concentration of 3.5 mol / L and a sulfate concentration of 5.8 mol / L. Vanadyl sulfate electrolyte.
[0102] The As content in the vanadyl sulfate electrolyte prepared in this comparative example was determined to be 4 ppm, which does not meet the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Redox Flow Batteries" for first-class quaternary electrolytes. Compared with Example 5, the pH of the sulfide precipitation in this comparative example is too high, and As 3+ Unable to communicate with S 2- Insoluble precipitate As2S3 is formed, and the arsenic ions in the V(IV) solution are not deeply removed, resulting in the arsenic ions being mixed in VO(OH)2 and entering the vanadium electrolyte, causing the arsenic content of the vanadium electrolyte to exceed the standard.
[0103] Comparative Example 6
[0104] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V43%, Al 0.1%, As 0.77%, Ca 0.1%, Fe 0.1%, K 0.1%, Mg 0.2%, Na 0.2%, and Si 0.8%, and the method comprises the following steps:
[0105] 1) After 100 g of high-arsenic vanadium-containing material and 0.42 g of elemental vanadium are mixed, the mixture is pressed into a block under a pressure of 50 MPa, and then calcined at a temperature range of 200° C. for 6 h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.05 wt%;
[0106] 2) The low-arsenic vanadium-containing material was dissolved in 750 mL of a 50 g / L KOH solution at 20° C., the stirring rate was 200 r / min, the leaching time was 4 h, and the potassium vanadate solution was filtered to obtain a potassium vanadate solution, and then the potassium vanadate solution was cooled to 1° C. at a rate of 0.1° C. / min, and the solution was stirred at a rate of 400 r / min during the cooling period. After cooling, potassium vanadate crystals were filtered to obtain potassium vanadate crystals, and then the low-arsenic vanadium-containing material was replaced with potassium vanadate crystals as a raw material, and step 2) was repeated twice to obtain 120 g of high-purity potassium vanadate crystals with an arsenic content of 0.06 wt% and a purity of 99.9%;
[0107] 3) The high-purity potassium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to -1, 15 g of formic acid is added, and the reaction is carried out at 50°C for 2 hours to obtain a V(IV) solution. The pH value of the V(IV) solution is adjusted to 5 with KOH, and 1.26 g of K2S (0.315 g each time) is added in 4 times, and the reaction is carried out at 2°C for 1 hour. The arsenic-free solution having an As content of 31.2 ppm is filtered to obtain the arsenic-free solution. The pH value of the arsenic-free solution is adjusted to 9 with KOH, and VO(OH)2 solid is filtered to obtain the VO(OH)2 solid. The VO(OH)2 solid is washed twice with a dilute sulfuric acid solution having a pH of 6.5, and then washed three times with pure water, and dissolved with 180 ml of a 5.5 mol / L sulfuric acid solution to obtain a vanadium concentration of 2.5 mol / L and a sulfate concentration of 5.2 mol / L vanadyl sulfate electrolyte.
[0108] The As content in the vanadyl sulfate electrolyte prepared in this comparative example was determined to be 1.5 ppm, which does not meet the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Redox Flow Batteries" for first-class 4-valent electrolytes. Compared with Example 6, the temperature during the sulfidation precipitation in this comparative example was too low, and the As content in the V(IV) solution was 3+ With S 2- The reaction activity is poor, and the precipitation cannot be generated and removed in time, resulting in arsenic ions being mixed in VO(OH)2 and entering the vanadium electrolyte, causing the arsenic content of the vanadium electrolyte to exceed the standard.
[0109] Comparative Example 7
[0110] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V52%, Al 0.1%, As 0.84%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0111] 1) After 50g of high-arsenic vanadium-containing material and 6.5g of VO2 were mixed, the mixture was pressed into a block under a pressure of 100MPa, and calcined at a temperature range of 450°C for 5h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.07wt%;
[0112] 2) dissolving the low-arsenic vanadium-containing material in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, stirring at a rate of 50 r / min, and leaching for 1 h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 2° C. at a rate of 8° C. / min, stirring the solution at a rate of 80 r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) twice to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.06 wt% and a purity of 99.92%;
[0113] 3) The high-purity potassium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid and the pH value is adjusted to 2.5. 48 g of potassium oxalate is added and the reaction is carried out at 99° C. for 0.5 h to obtain a V(IV) solution. The pH value of the V(IV) solution is adjusted to 0 with dilute sulfuric acid. 1.056 g of K2S is added at one time and the reaction is carried out at 99° C. for 1 h. The arsenic-free solution having an As content of 16 ppm is obtained by filtration. The pH value of the arsenic-free solution is adjusted to 5 with KOH. The VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution having a pH of 6.5, and then washed three times with pure water. The VO(OH)2 solid is dissolved in 200 ml of a 6 mol / L sulfuric acid solution to obtain a vanadium concentration of 2 mol / L and a sulfate concentration of 5.8 mol / L. Vanadyl sulfate electrolyte.
[0114] The As content in the vanadyl sulfate electrolyte prepared in this comparative example was determined to be 2.6 ppm, which does not meet the requirements of GB / T 37204-2018 "Electrolyte for All-vanadium Redox Flow Batteries" for first-class 4-valent electrolytes. Compared with Example 7, the arsenic removal precipitant in this comparative example was added once, resulting in a decrease in the S content in the V(IV) solution. 2- The concentration increases instantly, S 2- With H in solution + Rapidly generate H2S gas, thereby reducing the S content in the solution 2- The amount of As in V(IV) solution 3+Failure to effectively precipitate and achieve deep removal, As 3+ It enters the electrolyte in the presence of VO(OH)2, causing the arsenic content in the vanadium electrolyte to exceed the standard.
[0115] Comparative Example 8
[0116] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V52%, Al 0.1%, As 0.84%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0117] 1) 50 g of high-arsenic vanadium-containing material was dissolved in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, with a stirring rate of 50 r / min and a leaching time of 1 h. The potassium vanadate solution was filtered to obtain a potassium vanadate solution, and then the potassium vanadate solution was cooled to 2° C. at a rate of 8° C. / min. During the cooling period, the solution was stirred at a rate of 80 r / min. After cooling, potassium vanadate crystals were filtered to obtain potassium vanadate crystals. Then, the low-arsenic vanadium-containing material was replaced with potassium vanadate crystals as a raw material and step 2) was repeated twice to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.4 wt% and a purity of 99.8%;
[0118] 2) The high-purity potassium vanadate crystals obtained in step 1) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 2.5, 48g of potassium oxalate is added, and the reaction is carried out at 99°C for 0.5h to obtain a V(IV) solution, the pH value of the V(IV) solution is adjusted to 0 with dilute sulfuric acid, and 1.056g of K2S (0.352g each time) is added in three times, and the reaction is carried out at 99°C for 1h, and the arsenic-free solution with an As content of 40ppm is obtained by filtering, and the pH value of the arsenic-free solution is adjusted to 5 with KOH, and VO(OH)2 solid is obtained by filtering. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution with a pH of 6.5, and then washed three times with pure water, and dissolved with 200ml of a 6mol / L sulfuric acid solution to obtain a vanadium oxysulfate electrolyte with a vanadium concentration of 2mol / L and a sulfate concentration of 5.8mol / L.
[0119] It was determined that the As content in the vanadyl sulfate electrolyte prepared in this comparative example was 16.9 ppm, which did not meet the requirements of GB / T 37204-2018 "Electrolyte for All-Vanadium Redox Flow Battery" for first-class 4-valent electrolyte. Compared with Example 7, this comparative example did not have a reduction roasting arsenic removal step to remove arsenic from the high-arsenic vanadium-containing material, and only relied on crystallization and precipitation to remove arsenic, resulting in reduced arsenic removal effect, and the arsenic content in the vanadium electrolyte exceeded the standard.
[0120] Comparative Example 9
[0121] A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, wherein the main components of the high-arsenic vanadium-containing material include V52%, Al 0.1%, As 0.84%, Ca 0.1%, Fe 0.2%, K 0.1%, Mg 0.3%, Na 0.2%, and Si 1.5%, and the method comprises the following steps:
[0122] 1) After 50g of high-arsenic vanadium-containing material and 6.5g of VO2 were mixed, the mixture was pressed into a block under a pressure of 100MPa, and calcined at a temperature range of 450°C for 5h under an argon atmosphere to obtain a low-arsenic vanadium-containing material with an arsenic content of 0.07wt%;
[0123] 2) dissolving the low-arsenic vanadium-containing material in 500 mL of a 250 g / L KOH solution at 80° C. for leaching, stirring at a rate of 50 r / min, and leaching for 1 h, filtering to obtain a potassium vanadate solution, then cooling the potassium vanadate solution to 2° C. at a rate of 8° C. / min, stirring the solution at a rate of 80 r / min during the cooling period, filtering to obtain potassium vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with potassium vanadate crystals as a raw material and repeating step 2) twice to obtain 100 g of high-purity potassium vanadate crystals with an arsenic content of 0.06 wt% and a purity of 99.92%;
[0124] 3) The high-purity potassium vanadate crystals obtained in step 2) are dissolved in dilute sulfuric acid, and the pH value is adjusted to 2.5, 48 g of potassium oxalate is added, and the reaction is carried out at 99° C. for 0.5 h to obtain a V(IV) solution with an As content of 21 ppm, and the pH value of the V(IV) is adjusted to 5 with KOH, and VO(OH)2 solid is obtained by filtration. The VO(OH)2 solid is washed once with a dilute sulfuric acid solution with a pH of 6.5, and then washed 3 times with pure water, and dissolved in 200 ml of a 6 mol / L sulfuric acid solution to obtain a vanadium concentration of 2 mol / L and a sulfate concentration of 5.8 mol / L. Vanadyl sulfate electrolyte.
[0125] The As content in the vanadium sulfate electrolyte prepared in this comparative example was determined to be 5.5 ppm, which does not meet the requirements of GB / T 37204-2018 "Electrolyte for All-Vanadium Redox Flow Batteries" for first-class 4-valent electrolytes. Compared with Example 7, this comparative example does not have a precipitation method for arsenic removal, resulting in the failure to deeply remove the residual arsenic in the V (IV) solution, and the arsenic content in the vanadium electrolyte exceeds the standard.
[0126] It should be noted that, according to the above embodiments of the present invention, those skilled in the art can fully realize the full scope of the independent claims and dependent rights of the present invention, and the implementation process and method are the same as the above embodiments; and the part not described in detail in the present invention belongs to the well-known technology in the field. However, the protection scope of the present invention is not limited to this, and any changes or substitutions that can be easily thought of by any person familiar with the field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a vanadium electrolyte using a high-arsenic vanadium-containing material, characterized in that: The steps include: 1) After mixing the high-arsenic vanadium-containing material and the arsenic removal reducing agent in a ratio of 2-9 times the theoretical content of the arsenic removal reducing agent required for reducing As(V) to As(III), the mixture is pressed into blocks at a pressure of 50-150 MPa, and calcined at a temperature range of 200-700°C for 1-6 h in an inert atmosphere to obtain a low-arsenic vanadium-containing material; 2) using alkaline solution to leach low-arsenic vanadium-containing material at 20-99°C, stirring the solution at a speed of 50-200 r / min for 1-4h, filtering to obtain a vanadate solution, then cooling the vanadate solution to 0-40°C at a rate of 0.1-5°C / min, stirring the solution at a rate of ≤400 r / min during the cooling period, filtering to obtain vanadate crystals after cooling, and then replacing the low-arsenic vanadium-containing material with vanadate crystals as raw materials to repeat step 2) multiple times to obtain high-purity vanadate crystals; 3) dissolving the high-purity vanadate crystals obtained in step 2) in acid, adjusting the pH value to 1-5, adding a reducing agent according to 1.2-3 times the theoretical content of the reducing agent required for reducing V(V) to V(IV), reacting at 20-99° C. for 0.5-5 h to obtain a V(IV) solution, adjusting the pH value of the V(IV) solution to -1-5, adding an arsenic removal precipitant in multiple times according to 2-8 times the theoretical amount of the arsenic removal precipitant required for removing As(III), reacting at 20-99° C. for 0.5-2 h, filtering to obtain an arsenic removal solution, adjusting the pH value of the arsenic removal solution to 5-12, filtering to obtain a VO(OH)2 solid, washing the VO(OH)2 solid with acid and water, and dissolving the washed VO(OH)2 with acid to prepare a vanadium electrolyte; wherein the reducing agent comprises one or more of sodium sulfide, elemental sulfur, sulfur dioxide, sulfite, oxalic acid, oxalate, glucose, fructose, sucrose, and formic acid.
2. The method according to claim 1, characterized in that The high-arsenic vanadium-containing material includes one or more of red vanadium with an arsenic content of ≥0.1 wt%, crude V2O5, ammonium polyvanadate, and ammonium metavanadate.
3. The method according to claim 1, characterized in that The high-arsenic vanadium-containing material contains 70-98wt% V2O5; the high-arsenic vanadium-containing material is obtained by a vanadium extraction process of waste SCR catalyst, stone coal and / or bauxite.
4. The method according to claim 1, characterized in that In step 1), the arsenic removal reducing agent includes one or more of metal vanadium, VO, V2O3, and VO2.
5. The method according to any one of claims 1 to 4, characterized in that: In step 2), the alkali solution includes one or more of NaOH and KOH solutions with a concentration of 50-500 g / L.
6. The method according to any one of claims 1 to 4, characterized in that: The multiple times in step 2) is 2 to 4 times.
7. The method according to any one of claims 1 to 4, characterized in that: The pH value is adjusted specifically as follows: when the pH value needs to be lowered, one or more acids including sulfuric acid and hydrochloric acid are added to the solution for adjustment; when the pH value needs to be increased, one or more bases including NaOH, KOH, and NH3 are added to the solution for adjustment.
8. The method according to any one of claims 1 to 4, characterized in that: The arsenic removal precipitant includes one or more of sodium sulfide, potassium sulfide, ammonium sulfide, hydrogen sulfide, and thiourea.
9. The method according to any one of claims 1 to 4, characterized in that: The multiple times in step 3) is 3 to 5 times.
10. The method according to any one of claims 1 to 4, characterized in that: In step 3), the reagent used for the acid washing is dilute sulfuric acid with a pH of 5 to 7, the number of washing times for the acid washing is 1 to 3 times, and the number of washing times for the water washing is 2 to 3 times; the reagent used for the acid dissolution is sulfuric acid with a concentration of 4 to 6 mol / L.
Citation Information
Patent Citations
Preparation method for vanadyl sulfate electrolyte of all-vanadium flow battery
CN102683733A
Method for preparing vanadyl sulfate electrolyte through reduction of ferrous sulfate / oxalic acid
CN104064799A
Method for producing high-purity ammonium metavanadate by deeply removing cobalt from vanadium raw material
CN114314661A
Crude vanadium purification method and application thereof
CN115747525A
Method for preparing high-concentration vanadium electrolyte through vanadate crystallization purification-chemical reduction
CN116404220A